Relationship of Physician‐identified Patient Race and Ethnicity to Use of Computed Tomography in Pediatric Blunt Torso Trauma. (18th April 2016) - Natale, JoAnne E.; Joseph, Jill G.; Rogers, Alexander J.; Tunik, Michael; Monroe, David; Kerrey, Benjamin; Bonsu, Bema K.; Cook, Lawrence J.; Page, Kent; Adelgais, Kathleen; Quayle, Kimberly; Kuppermann, Nathan; et al.
Abstract: Objectives: The objective was to determine whether a child's race or ethnicity as determined by the treating physician is independently associated with receiving abdominal computed tomography (CT) after blunt torso trauma. Methods: We performed a planned secondary analysis of a prospective observational cohort of children < 18 years old presenting within 24 hours of blunt torso trauma to 20 North American emergency departments (EDs) participating in a pediatric research network, 2007–2010. Treating physicians documented race/ethnicity as white non‐Hispanic, black non‐Hispanic, or Hispanic. Using a previously derived clinical prediction rule, we classified each child's risk for having an intra‐abdominal injury undergoing acute intervention to define injury severity. We performed multivariable analyses using generalized estimating equations to control for confounding and for clustering of children within hospitals. Results: Among 12, 044 enrolled patients, treating physicians documented race/ethnicity as white non‐Hispanic ( n = 5, 847, 54.0%), black non‐Hispanic ( n = 3, 687, 34.1%), or Hispanic of any race ( n = 1, 291, 11.9%). Overall, 51.8% of white non‐Hispanic, 32.7% of black non‐Hispanic, and 44.2% of Hispanic children underwent abdominal CT imaging. After age, sex, abdominal ultrasound use, risk for intra‐abdominal injury undergoing acute intervention, and hospital clustering were adjusted for, the likelihood of receiving an abdominal CT was lower (odds ratio [OR] = 0.8, 95% confidence interval [CI] = 0.7 to 0.9) for black non‐Hispanic than for white non‐Hispanic children. For Hispanic children, the likelihood of receiving an abdominal CT did not differ from that observed in white non‐Hispanic children (OR = 0.9, 95% CI = 0.8 to 1.1). Conclusions: After blunt torso trauma, pediatric patients identified by the treating physicians as black non‐Hispanic were less likely to receive abdominal CT imaging than those identified as white non‐Hispanic. This suggests that nonclinical factors influence clinician decision‐making regarding use of abdominal CT in children. Further studies should focus on explaining how patient race can affect provider choices regarding ED radiographic imaging.